FRI0310 Long-term mortality and complications in young and elderly patients with anca-associated vasculitis. (15th June 2017) - Berti, A; Felicetti, M; Padoan, R; Brunori, G; Schiavon, F; Paolazzi, G
Abstract : Background: Advancing age is a risk factor for complications and mortality in anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). 1, 2 Objectives: To analyze differences in infectious, metabolic and cardiovascular complications, renal function, and mortality in patients diagnosed with AAV before or after 65 years of age, and followed for up to 5 years. Methods: We retrospectively collected long-term clinical and laboratory data of AAV patients of two referral centers in Northern Italy from 2000, and grouped patients in young (YP, <65 years old) and elderly (EP, ≥65 years old). Results: Of the 114 patients included, 83 had a follow-up of at least 2 years (58 YP vs 25 EP). Median follow-up was 55 [32–100] months in YP and 44 [18–59] months in EP (p<0.013). 86.1% (68 patients) and 62.9% (22 patients) were diagnosed with GPA in YP and EP subsets, respectively. At baseline, YP and EP patients were similar in terms of BVAS/WG score, glomerulonephritis and alveolar hemorrhage, whereas creatinine levels (1.1 mg/dL [0.8–2.3] vs 1.82 mg/dL [0.98–3.5], p=0.044), renal insufficiency rate (44.7% vs 67.6%, p=0.026) and ANCA pattern (PR3 67.5% vs 26.5%, MPO 19.5% vs 59.8%; p<0.001 for both comparisons) were different in YR and ER, respectively. No significant difference in induction and maintenance regimens was found in the two groups, nor in clinical remission rate after induction treatment (all p>0.05). At 2 year, creatinine levels (YP 1.0 mg/dL [0.85–1.31], EP 1.2 mg/dL [1.1–2.2]) and renal insufficiency rate decreased within each group (p<0.05). End-stage renal disease, hypertension rate, cardiac or cerebral ischemic attack rate, diabetes, solid or hematological cancer rate and mean vasculitis damage index were not statistically different in the two groups, whereas heart failure was more represented in EP (0.0% vs 8.3%, p=0.027). Within the first 5 years of follow-up, severe infection (requiring hospitalization) and mortality rates were significantly higher in EP group when compared with YP group (p=0.024 and p=0.010 by Kaplan-Meier analysis, respectively, Figure 1 ), mirrored by a higher annual severe infection rate (p=0.041; 0.22±0.69 versus 0.05±0.17) and annual mortality rate (p=0.001; 0.33±1.02 versus 0.01±0.08) in EP group. Relapse rate was similar in YP and EP within 5 years (Figure 1 ). Lymphopenia rate (at least 1 event, <1000x10 9 /L) was significantly higher in EP only at 6 month (p<0.05), whereas severe lymphopenia (<500x10 9 /L), leukopenia (<4000x10 9 /L) or hypogammaglobinemia (Ig<5g/L) rates were similar in both groups during the follow-up. Persistent lymphopenia (≥12months, <1000x10 9 /L) was detected in 3 patients after cyclophosphamide treatment (2 YP and 1 EP). Only relapse before 2 years of follow-up was associated with infections in YP (p<0.001, OR 4.0 [CI 95%, 1.2–13.3]), but not in EP. Conclusions: Heart failure is more frequent in older patients, which have higher infection and mortality rates. Transient lymphopenia is significantly higher in EP after induction treatment, but is not associated with their increase in infectious events. Despite a similar incidence of relapse in YP and EP, relapsing disease associates with infectious events in YP, but not in EP. References: Flossmann O et al. Ann Rheum Dis. 2011 Mar;70(3):488–94. Timlin H et al. Semin Arthritis Rheum. 2015 Aug;45(1):67–9. Disclosure of Interest: None declared